Experimental Research on Longitudinal Steel Bar Bond Properties in Modified Recycled Aggregate Concrete Beam-Column Interior Joint under Cyclic Loading - Jia-Li Fu; Bing-Kang Liu; Jun-Wei Ma (Advances in Materials Science and Engineering)
Three recycled aggregate concrete (RAC) beam-column interior-joint specimens (including two modified recycled aggregate concrete interior joints with replacement of fly ash ratio of 15%) were tested under cyclic loading in order to study the bond behavior of the longitudinal steel bar at RAC joint. The tests obtained load-strain hysteresis curves of longitudinal bars. The relative bond strength of longitudinal bar in characteristic stages was calculated. The test results indicated that the longitudinal steel bar in RAC joint is able to supply a stable bond stress both in the full crack stage and in the ultimate stage, meaning that the requirements of stress transferring and displacement coordinating between RAC and reinforcements can be satisfied. The larger the diameter of steel bar, the more serious the bond strength degradation. The RAC with fly ash can improve the interface compactness and bond strength of recycled aggregate in full crack stage. When beam-column interface of concrete compression zone reaches ultimate strain, the compressive stress of the longitudinal reinforcement cannot be exerted. The bond stress of the steel bar cannot realize the pull and compressive stress conversion in the length of the core area of the joint owing to the stress hysteresis of the compression rebars.